EDUCATION LEADERSHIP - Haliza, Siti; Razak, Ahmad Zabidi Abdul (DIVERSITY Logic Journal Multidisciplinary, 2023)
Background. Leadership is the process by which a leader impacts the conduct of his subordinates in order for them to collaborate and work successfully in order for the organization's goals to be met. Research Purpose. This research aims to determine education leadership. Research Method. By gathering literature (material materials) from books, journals, and other sources pertaining to the field of educational administration, researchers employ the literature study approach. In order to create the article, more precise information on educational leadership resources will be gathered from these sources. The material will thereafter be arranged and modified to fit relevant conversations. Findings. The leadership style of a leader in inspiring personnel to carry out corporate operations will decide the firm's or organization's effectiveness. A number of employees expect to be treated by leaders who are open and flexible in their work, while others hope that the leadership corrects more bad work because this will make subordinates work less productive and less participative in decision making. Conclusion. Leadership is a branch of management that includes planning and organizing, but its primary job is to persuade others to achieve their goals.